The Tendency of People to Choose Gold Investment Over Investment in the Capital Market From the Perspective of Islamic Financial Management - Najiatun, Najiatun; Khalida, Nur Diana; Firdaus, Jannatul; Hidayat, Nurul (Majapahit Journal of Islamic Finance and Management, 2025)
Investment in Islam is not solely focused on the extent of material profits to be gained through economic activities; rather, the concept of investment in Islam is driven by certain dominant factors. Gold investment is the most popular investment among the public. The author used a qualitative research method with descriptive analysis in this study. Qualitative research involves collecting data in a natural setting with the aim of interpreting the phenomena that occur. The results of this study are as follows: First, investing in gold is very easy and carries minimal risk. Second, the price of gold investments consistently increases over time, which is what attracts public interest. Third, gold investment can be done by anyone without requiring specialized knowledge.